EKSPLOITASI HUTAN DI WILAYAH “DAJAK BESAR” (GROOT DAJAK) DAN “BANDJAR” PADA MASA FEDERAL - Rydho Bagus Pratama (Lambung Mangkurat University, 2026)
This article examines forest exploitation under the authority of state administrations in Kalimantan, with particular reference to Great Dajak and Bandjar. Following the end of the Second World War, the Dutch government reasserted its presence in the Dutch East Indies and initiated the establishment of federal states within the framework of the Dutch-Indonesian Union. In Kalimantan, these states were administered by councils endowed with domestic authority, including jurisdiction over the forestry sector. Control over natural resources, including forests, was regulated under the “Zelfbestuursregelen 1938”, which conferred extensive authority upon regional governments to manage resources within their respective territories. The Dutch authorities capitalised on this regulatory framework by delegating such powers to local councils while simultaneously advancing their economic interests in Kalimantan. On 4 February 1948, the Great Dajak Council convened to grant a forestry concession to an Indonesian-Dutch joint venture, Bruynzeel-Dajak. Subsequently, on 24 June 1949, the Dutch conferred eight domains of authority upon the Bandjar Council, one of which encompassed forestry administration. This study employs the historical method. The findings demonstrate that, first, during the federal period, local governments exercised significant authority over the management of natural resources, particularly forestry, as stipulated under the “Zelfbestuursregelen 1938” and reinforced by Dutch policy. Second, the delegation of authority in the forestry sector facilitated the establishment of modern timber enterprises in the Great Dajak region, while in the Bandjar region it stimulated the growth of local timber entrepreneurs and the proliferation of timber-processing facilities.Keywords: Forestry; Exploitation; Dajak Besar; Bandjar; Kalimantan